La comunicación, como una estrategia adicional para la gestión del cambio organizacional en Asecofin S.A.S - Torres García, Juliana Andrea (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
The present work consists of the design and documentation work of different communication strategies aligned to a change management methodology in the implementation of the quality management system of Asecofin SAS. Upon arriving at Asecofin, it was evident that there was no communication in or between his processes, their collaborators did not perceive themselves motivated, listened to, valued or empowered. As it is a family organization, it was highlighted that all decisions were centralized in the general manager, although they worked in the development of the quality management system many of its collaborators and Contractors did not know about this project, they had tools like Moodle underutilized and their communications were deficient as they lacked strategy and objective. As in any organization, Asecofin's internal and external client must know the benefits of implementing a quality management system with the objective of achieving continuous improvement. To do this, use the NTP methodology 581: "Management of organizational change" (National Institute of Safety and Hygiene at Work, 2001). And I designed, developed and implemented different strategies of communication to disseminate the QMS articulated with change management. I conducted a general survey in the organization prior to the start of the project that evidenced the centralization of decision-making and the blockages that this produced, the lack of communication with all hierarchical levels, the perception of apathy on the part of Asecofin with its collaborators and contractors, the lack of training and empowerment of employees and the need to transform a tax communication by a participatory communication and in double via. After the stage of implementation and validation of the results, I found a much more cohesive panorama in the organization. Thanks to the strategies communication the perception of collaborators, contractors and clients change favorably giving Asecofin the opportunity to be an organization that supports business sustainability on communication.

El presente trabajo, consiste en el diseño y documentación de diferentes estrategias de comunicación alineadas a una metodología de gestión del cambio en la implementación del sistema de gestión de calidad de Asecofin SAS. Al llegar a Asecofin evidencie que no había comunicación en ni entre sus procesos, sus colaboradores no se percibían motivados, escuchados, valorados ni empoderados. Al tratarse de una organización familiar se resaltaba que todas las decisiones se centralizaban en el gerente general, aunque trabajaban en el desarrollo del Sistema de gestión de calidad muchos de sus colaboradores y contratistas no sabían de este proyecto, tenían herramientas como Moodle subutilizadas y sus comunicaciones eran deficientes ya que carecían de estrategia y objetivo. Como en cualquier organización, el cliente interno y externo de Asecofin debe conocer los beneficios de implementar un sistema de gestión de calidad con el objetivo de lograr el mejoramiento continuo. Para ello use la metodología NTP 581: “Gestión del cambio organizativo” (Instituto Nacional de Seguridad e Higiene en el Trabajo, 2001). Y diseñé, desarrollé e implemente diferentes estrategias de comunicación para divulgar el SGC articulado con la gestión del cambio. Realicé una encuesta general en la organización previa al inicio del proyecto que evidenció la centralización de la toma de decisiones y los bloqueos que esto producía, la falta de comunicación con todos los niveles jerárquicos, la percepción de apatía por parte de Asecofin con sus colaboradores y contratistas, la falta de capacitación y empoderamiento de los colaboradores y la necesidad de transformar una comunicación impositiva por una comunicación participativa y en doble vía. Pasada la etapa de implementación y validación de los resultados, encontré un panorama mucho más cohesionado en la organización. Gracias a las estrategias de comunicación la percepción de los colaboradores, contratistas y clientes cambio favorablemente dándole a Asecofin la oportunidad de ser una organización que soporta sobre la comunicación la sostenibilidad empresarial.
Keywords: Comunicaciones; Gestión del cambio; Cultura organizacional; Satisfacción del cliente; Communications; Change management; Organizational culture; Customer satisfaction